Geographical information system counter position at PT. Web-based Millennium Plaza - Sri Hartati (IHSA Institute, 2022)
The development of computer technology has a positive impact on all life, especially in the world of industry, education, government and small to medium businesses. Where with the existence of computer technology all work done manually can be done computerized. A well-designed information system will greatly assist organizations or companies in obtaining accurate, timely and relevant information in their presentation. PT. Millennium Plaza is one of the many companies engaged in counter rental services in the city of Medan. In this case the author designed an information system that supports company performance, namely